2022
DOI: 10.3390/molecules27092914
|View full text |Cite
|
Sign up to set email alerts
|

Chemometric Investigation and Antimicrobial Activity of Salvia rosmarinus Spenn Essential Oils

Abstract: To ensure the better production and sustainable management of natural resources, a chemometric investigation was conducted to examine the effect of cooperative and harvesting periods on the crop yields and chemical compositions of Salvia rosmarinus Spenn essential oils in the Oriental region of Morocco. The samples were collected from three cooperatives over nine time periods from January 2018 to April 2019. The chemical composition of Salvia rosmarinus Spenn essential oils was analyzed by gas chromatography c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…rosmarinus EO (81.64 ± 3.02%), followed by hydrocarbon monoterpene (17.63 ± 1.41%), whereas sesquiterpenes were detected in much lower amounts. This composition is similar to that found by Annemer et al and Sabbahi et al, who also harvested in the Province of Figuig, the Oriental region of Morocco. The S.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…rosmarinus EO (81.64 ± 3.02%), followed by hydrocarbon monoterpene (17.63 ± 1.41%), whereas sesquiterpenes were detected in much lower amounts. This composition is similar to that found by Annemer et al and Sabbahi et al, who also harvested in the Province of Figuig, the Oriental region of Morocco. The S.…”
Section: Resultsmentioning
confidence: 99%
“…atlantica sawdust was collected from a cedarwood sawmill in Azrou (the Middle Atlas Mountains in Morocco) (latitude 33°26′9.226″N, longitude 5°13′21.104″W). All plants were collected during the same periodin Aprilbecause it is the best time to exploit rosemary . The herb should be dried in a shady place at an ambient temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Rosemary extracts are generally less active against gramnegative bacteria than gram-positive bacteria (Annemer et al, 2022;Manilal et al, 2021). Annemer et al (2022) compared the susceptibility of two gram-positive bacteria (Mycobacterium smegmatis and B. subtilis) and one gram-negative bacteria (E. coli) under the treatment with rosemary extracts, and the results revealed the MIC value of rosemary extract against the two tested gram-positive bacteria was 1/500 (v/v), which was slightly more potent than that of E. coli (v/v = 1/250). Manilal et al (2021) demonstrated that these results might be attributed to the distinctive differences in cell membrane structure between gram-positive and gram-negative bacteria.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Annemer et al. (2022) compared the susceptibility of two gram‐positive bacteria ( Mycobacterium smegmatis and B. subtilis ) and one gram‐negative bacteria ( E. coli ) under the treatment with rosemary extracts, and the results revealed the MIC value of rosemary extract against the two tested gram‐positive bacteria was 1/500 (v/v), which was slightly more potent than that of E. coli (v/v = 1/250). Manilal et al.…”
Section: Biological Activities Of Rosemary Extractmentioning
confidence: 99%
“…C. atlantica sawdust was collected from a cedarwood sawmill in Azrou (the Middle Atlas Mountains in Morocco) (latitude 33°26'9.226"N, longitude 5°13'21.104"W). All plants were collected during the same period-in April-because it is the best time to exploit rosemary (Annemer et al 2022). The herb should be dried in a shady place at an ambient temperature.…”
Section: Plant Materialsmentioning
confidence: 99%